Krull dimension of affinoid enveloping algebras of semisimple Lie algebras - Ardakov, K; Grojnowski, I (Cambridge University Press, 2013)
Using Beilinson–Bernstein localisation, we give another proof of Levasseur's theorem on the Krull dimension of the enveloping algebra of a complex semisimple Lie algebra. The proof also extends to the case of affinoid enveloping algebras.